Pendidikan Humanis Perspektif Muhammad Abduh: Relevansinya bagi Penguatan Pendidikan Karakter di Era Digital - Nafilatul Munawwaroh, Siti; Fahmi, Muhammad; Nur Fauziyah Amaliyah, Intan (IAIN Kendari, 2025)
This study critically examines Muhammad Abduh’s concept of humanistic education (al-tarbiyah al-insāniyyah) and its philosophical relevance to strengthening Islamic character education amid the moral and ethical crises of the digital era. The research is motivated by increasing challenges such as digital alienation, misinformation, and spiritual disengagement that accompany technological disruption and moral decline in modern education. Using a qualitative library research approach, this study systematically analyzes Abduh’s primary works Risālat al-Tauḥīd and Tafsīr al-Manār and synthesizes them with contemporary Islamic educational literature published within the last five years. The data were interpreted through content and hermeneutic analysis to uncover the underlying philosophical principles of Abduh’s thought and to relate them to contemporary digital learning challenges and ethical dilemmas. The findings indicate that Abduh’s humanistic framework, rooted in theocentric rationalism, is built upon three interrelated pillars: rationality and freedom of thought (‘aql), the integration of knowledge and morality (‘ilm wa akhlāq), and social-spiritual responsibility (mas’uliyyah ijtimā‘iyyah wa rūhiyyah). The study concludes that Abduh’s theocentric humanism provides a solid philosophical foundation for constructing an adaptive, ethical, and human-centered paradigm of Islamic character education capable of responding to the global moral challenges of the digital age.